Expansion of higher education and inequality of opportunities: a cross-national analysis. Issue 3 (3rd May 2016) - Liu, Ye; Green, Andy; Pensiero, Nicola
ABSTRACT: This study extends the comparative model of country groups to analyse the cross-national trends in the higher education expansion and opportunities. We use descriptive data on characteristics and outcomes of higher education systems in different countries groups, including the liberal market countries, the social democratic countries, the Mediterranean countries, the German-speaking countries, the Northern states, and the East Asian societies. At the theoretical level, we assess the validity of the maximally maintained inequality (MMI) theory in the cross-national contexts. We confirm the MMI theory in general patterns of the expansion of higher education opportunities; however, we argue that it is not sufficient to provide accounts on specific country differences in the strength of the relationship between participation rates and inequality of opportunities. Therefore, we explain the divergences from the general pattern of higher participation being associated with lower inequality. We propose three main contenders including the private contribution to higher education, less hierarchical higher education systems, and the participation in the dual higher education system and greater public support and entitlements. We use a series of indicators on the trends of participation in higher education and different types of universities, the private contribution to higher education, and the trends of public support and entitlements to assess the three contenders. Thus, we argue that there are different patterns of the trade-offs between expansion and equalising opportunities. Most rapid expansion is observed in countries with high private contributions to higher education and little government support for students mainly because governments can then afford more places but equalisation of opportunities from the expansion in these systems is limited because of financial barriers to access to less well-off groups. Most egalitarian systems seem to have somewhat lower participation rates with lower fees and strong government support such as the social democratic and the German-speaking countries.